Knowledge, attitudes and practices relating to antibiotic use among community members of the Rupandehi District in Nepal - Anant Nepal; Delia Hendrie; Suzanne Robinson; Linda A. Selvey (BMC, 2019)
Abstract Background The development of antibiotic resistance is one of the biggest threats to global public health. Inappropriate use of antibiotics is recognised as a leading cause of antibiotic resistance. The aim of this study was to explore the knowledge, attitudes and practices (KAP) towards antibiotic use among adults in Nepal. Methods A quantitative survey was conducted with 220 community members of the Rupandehi district of Nepal, with cluster sampling techniques applied to select households. Interviews were carried out face-to-face using a structured questionnaire. Responses were presented using descriptive analysis, with chi-squared tests and regression analysis applied to identify factors associated with KAP about antibiotic use and the Spearman's rank order correlation coefficient calculated to examine the relationship between responses to the KAP questions. Results The sample comprised more females (54%) than males, the average age of respondents was 38.5 years and almost 60% of respondents lived in rural areas. Respondents had relatively good knowledge about aspects of antibiotic use other than identifying antibiotics. The concept of antibiotic resistance was well known but imperfectly understood. Half of respondents (50.9%) were unsure whether skipping doses would contribute to the development of antibiotic resistance, 88.2% indicated they would go to another doctor if not prescribed an antibiotic when they thought one was needed and nearly half (47.7%) believed antibiotics helped them get better more quickly if they had a fever. Most respondents reported correct practices accessing and using antibiotics, however, 84.6% at least sometimes preferred an antibiotic when they have a cough and sore throat. Logistic regression showed respondents with higher levels of education tended to have better knowledge, more appropriate attitudes and better practices about antibiotic use. Rural respondents were less likely to have better knowledge about antibiotic use, while females were more likely to report better practices. Conclusion The study provides baseline evidence about the knowledge, attitudes and practices regarding antibiotic use among the population of the Rupandehl district. Its findings will be useful in designing effective and targeted interventions to decrease misconceptions about antibiotic use and to increase awareness about the risks of inappropriate use of antibiotics in the community.